Using the ACORN Standards: An exploration of claims, concerns and issues - Carollyn Williams; Jed Duff; Pat Nicholson; Lois Hamlin; Brigid Gillespie (Journal of Perioperative Nursing)
An interactive action research workshop was offered during the ACORN & ASIORNA Conference which was held in Adelaide in 2018. The purpose of the workshop was to explore the research evidence supporting ACORN’s Standards for Perioperative Nursing in Australia, to identify gaps in the evidence related to  standards and to explore challenges associated with the implementation of standards in clinical practice. The workshop also provided perioperative nurses with the opportunity to discuss their research interests and ask questions about undertaking research-focused degrees. Workshop participants provided an eclectic and credible range of issues related to the development and implementation of standards, underpinned by their concern for patient safety. In addition, the workshop outcomes have since provided the basis for the Research Committee to develop a research priorities survey to be distributed to the membership in the next 12 months.